Protective effects of triptolide on retinal ganglion cells in a rat model of chronic glaucoma - Yang F; Wang DM; Wu LL; Li Y (Dove Medical Press, 2015)
Fan Yang, Dongmei Wang, Lingling Wu, Ying Li Ophthalmology Department, Peking University Third Hospital, Beijing, People’s Republic of China Purpose: To study the effects of triptolide, a Chinese herb extract, on retinal ganglion cells (RGCs) in a rat model of chronic glaucoma.Methods: Eighty Wistar rats were randomly divided into triptolide group (n=40) and normal saline (NS) group (n=40). Angle photocoagulation was used to establish the model of glaucoma, with right eye as laser treated eye and left eye as control eye. Triptolide group received triptolide intraperitoneally daily, while NS group received NS. Intraocular pressure (IOP), anti-CD11b immunofluorescent stain in retina and optic nerve, RGCs count with Nissel stain and microglia count with anti-CD11b immunofluorescence stain in retina flat mounts, retinal tumor necrosis factor (TNF)-α mRNA detection by reverse transcription–polymerase chain reaction, and double immunofluorescent labeling with anti-TNF-α and anti-CD11b in retinal frozen section were performed.Results: Mean IOP of the laser treated eyes significantly increased 3 weeks after photocoagulation (P<0.05), with no statistical difference between the two groups (P>0.05). RGCs survival in the laser treated eyes was significantly improved in the triptolide group than the NS group (P<0.05). Microglia count in superficial retina of the laser treated eyes was significantly less in the triptolide group (30.40±4.90) than the NS group (35.06±7.59) (P<0.05). TNF-α mRNA expression in the retina of the laser treated eyes in the triptolide group decreased by 60% compared with that in the NS group (P<0.01). The double immunofluorescent labeling showed that TNF-α was mainly distributed around the microglia.Conclusion: Triptolide improved RGCs survival in this rat model of chronic glaucoma, which did not depend on IOP decrease but might be exerted by inhibiting microglia activities and reducing TNF-α secretion. Keywords: glaucoma, triptolide, microglia, neuroprotection